A comparative study between intraarticular infiltration of platelet rich plasma and hyaluronic acid in osteoarthritis knee - Manju Jayaram; T. S., Channappa; Yatish R.; Shivskumar H. B.; Shuvam Singh (International Journal of Research in Orthopaedics, 2023)
Background: Osteoarthritis (OA) is the most common progressive musculoskeletal condition that can affect joints, but it mainly affects the hips and knees as predominant weight-bearing joints and is characterized by structural modifications to primarily articular cartilage and subchondral bone, Hoffa’s fat pad, synovia, ligaments and muscles, leading to the concept of OA as a whole joint disease. Hence the present study was undertaken to evaluate the outcomes of platelet rich plasma (PRP) and hyaluronic acid (HA) intra-articular injections in patients with OA in terms of pain by numerical pain score and VAS and to evaluate the outcomes of PRP and HA intra-articular injections in patients with OA in terms of functional outcome by WOMAC scores. Methods: The study was a prospective hospital-based study in Kempegowda Institute of Medical Sciences between 2020 to 2022. The study was conducted on 100 patients, more than the age of 50 years of either gender with grade I-III OA of the knee fulfilling the inclusion and exclusion criteria. Patients were followed up at 6, 12 and 24 weeks for data collection and data was analyzed after follow-up visits were completed for all patients. Results: On intragroup analysis, there was significant reduction in the mean WOMAC score in both the study groups across time-points (p<0.05). On intragroup analysis, there was significant reduction in the mean VAS score in both the study groups across time-points (p<0.05). On intergroup analysis at any time point of follow-up, the mean WOMAC score was noted to be statistically comparable between the study groups (p>0.05). Conclusions: In patients with symptomatic knee OA, intra-articular HA and PRP provide short term improvement in pain and function. Both the therapy agents for OA were associated with equivalent safety, with no complications.